1994
DOI: 10.1021/bi00179a010
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions Control the Parallel and Antiparallel Orientation of .alpha.-Helical Chains in Two-Stranded .alpha.-Helical Coiled-Coils

Abstract: The role of interchain electrostatic interactions in orientating alpha-helical chains to form two-stranded parallel and antiparallel coiled-coils has been investigated. Four disulfide-bridged coiled-coils were designed: parallel coiled-coils with interchain electrostatic attractions (P/A) and repulsions (P/R) and antiparallel coiled-coils with interchain electrostatic attractions (AP/A) and repulsions (AP/R). These coiled-coils were made by air oxidation of two 35-residue peptides with the appropriate heptad r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 78 publications
6
133
0
1
Order By: Relevance
“…These results strongly support our earlier contention that the difference in the estimates of their stabilities was due to the ionic property of GdnHCl and its absence in urea (Monera et al, 1993(Monera et al, , 1994. It is well understood that GdnHCl is a salt and, therefore, expected to ionize in aqueous solution.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results strongly support our earlier contention that the difference in the estimates of their stabilities was due to the ionic property of GdnHCl and its absence in urea (Monera et al, 1993(Monera et al, , 1994. It is well understood that GdnHCl is a salt and, therefore, expected to ionize in aqueous solution.…”
Section: Discussionsupporting
confidence: 90%
“…2B). Their CD profiles in benign medium showed that the 2 minima at 220 and 208 nm had a molar ellipticity ratio of -1, which had been previously attributed to coiled-coil structures (Lau et al, 1984;Zhou et al, 1992aZhou et al, , 1992bZhu et al, 1992;Monera et al, 1993Monera et al, , 1994. In the presence of TFE, which disrupts hydrophobic interactions, the CD profiles became more characteristic of single-stranded a-helices.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Thus, a design where the e and g positions have opposite polarities would result in interchain electrostatic attraction in the parallel topology, whereas residues with the same polarity would stabilize the antiparallel orientation. 14,15 The importance of electrostatic interactions was also evident in the case of the C-terminal domain from bovine inhibitor protein of F1 ATPase, which forms an antiparallel coiled-coil dimer but switches to tetramer above pH 6.5. 16 Another factor that affects the alignment of the helices is packing.…”
Section: Introductionmentioning
confidence: 97%